2022
DOI: 10.2147/jpr.s363743
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Patient-Controlled Intravenous Analgesia (PCIA) with Sufentanil Background Infusion for Post-Cesarean Analgesia: A Randomized Controlled Trial

Abstract: Purpose To investigate the effectiveness of sufentanil patient-controlled intravenous analgesia pump (PCIA) and background infusion in patients of post-cesarean analgesia. Patients and Methods This trial compared two groups of women undergoing cesarean section and receiving PCIA: no background infusion group (n=30), 6-min lockout time, and background infusion group (n=30), 2 mL/h infusion, 10-min lockout time. Both groups with 2 μg/kg sufentanil was diluted to 100 mL wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…If postoperative nausea/vomiting developed, azasetron (10 mg) intravenous injection was administered. If severe nausea persisted after two consecutive rescue antiemetics, PCIA was stopped for 2 h and restarted later when the symptoms subsided 13 . No treatment for pruritus and chills was performed due to the patients' tolerance.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…If postoperative nausea/vomiting developed, azasetron (10 mg) intravenous injection was administered. If severe nausea persisted after two consecutive rescue antiemetics, PCIA was stopped for 2 h and restarted later when the symptoms subsided 13 . No treatment for pruritus and chills was performed due to the patients' tolerance.…”
Section: Methodsmentioning
confidence: 99%
“…If severe nausea persisted after two consecutive rescue antiemetics, PCIA was stopped for 2 h and restarted later when the symptoms subsided. 13 No treatment for pruritus and chills was performed due to the patients' tolerance. A urinary catheter was reinserted in case of any urinary retention.…”
Section: Secondary Outcomesmentioning
confidence: 99%
See 2 more Smart Citations
“…[5] Some studies have reported that the incidence of uterine contraction pain is 30% to 40% among women in labor, [6] and 4% to 10% of women in normal labor may experience chronic pain. [7] Uterine contractions are associated with the elimination of malignant fluid and regeneration of the uterus. As the global population is gradually decreasing, women’s fertility and health are highly valued, and uterine contraction is a necessary part of every woman’s life, so uterine contraction pain should be taken seriously.…”
Section: Introductionmentioning
confidence: 99%